198k views
1 vote
-7p = -3p - 8
p =
Help

2 Answers

3 votes

Answer:


\huge{ \fbox{ \sf{p = 2}}}

Explanation:


\bigstar{ \sf{ \: - 7p = - 3p - 8}}


\underline{ \underline{ \mathfrak{Let's \: solve}}} :


\text{Step \: 1} : \sf{Move \: 3p \: to \: left \: hand \: side \: and \: change \: it's \: sign}


\mapsto{ \sf{ - 7p + 3p = - 8}}


\text{Step \: 2} : \sf{Collect \: like \: terms}


\sf{Like \: terms \: are \: those \: which \: have \: the \: same \: base}


\mapsto{ \sf{ - 4p = - 8}}


\text{Step \: 3} : \sf{Divide \: both \: sides \: by \: - 4}


\mapsto{ \sf{ ( - 4p)/( - 4) = ( - 8)/( - 4)}}


\text{Step \: 4} : \sf{Calculate}


\mapsto{ \sf{p = 2}}

Hope I helped!

Best regards! :D

~
\sf{TheAnimeGirl}

User Jorge Alvarado
by
5.3k points
5 votes

Answer:

p=2

Explanation:

-7p = -3p - 8

Add 3p to each side

-7p+3p = -3p+3p - 8

-4p = -8

Divide each side by -4

-4p/-4 = -8/-4

p = 2

User Georg Grab
by
5.7k points